Pelatihan dan Analisis Sistem Informasi Risiko dan Pengendalian Kualitas pada Pengembangan Perangkat Lunak di PT. Extramarks Education Indonesia - Bersello , Ruben; Putri, Fiqrotul Aulia; W, Raditya Galih (Publikasi Pengabdian Masyarakat Komputer dan Teknologi (PUNDIMASKOT), 2025)
In the digital transformation era, managing risks and quality control in software development has become crucial for the success of technology products, particularly in the education sector. This training aimed to enhance participants' understanding of risk information system analysis and quality control in the development of "Kelas Pintar" software at PT. Extramarks Education Indonesia. The training materials covered risk identification, creation of Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and User Interface (UI) design. The training method employed direct observation, interviews, literature studies, case studies, and simulations of risk analysis and quality control. Evaluation was conducted through analysis of participants' work results, including DFDs, ERDs, and system improvement recommendations. The results showed a significant increase in participants' understanding of the importance of risk information systems and quality control implementation, as well as technical skills in system analysis documentation. These findings highlight the importance of practice-based training in supporting the development of high-quality and secure software.